Advances in the implementation of optical fiber on structures. The present of an implementation with a future - Alegre, Vicente; Villalba, Sergio (Revista ALCONPAT, 2021)
An example of a real case is discussed in which, on an existing tunnel, which is instrumented with optical fiber, a building is built. This makes possible to track the load history of a structure since the fiber is placed. To verify that the tunnel is not structurally affected during the construction period, sections of it are instrumented and the micro deformations that occur are measured, which are compared with those of the model. It has been possible to appreciate the ovalizations and tensions in the vault during the different phases of the construction process, all of them being below the limit values established in the contingency plan. This technique has made possible to validate the works carried out throughout the process.